Understanding the Resistance to Use Metaverse Shopping Platforms in Sarawak, Malaysia: An Investigation by Using Innovation Resistance Theory - Chin, Chee Hua, Dr; Chiew, Evelyn Cai-Ni; Tiong, Karment (UI Scholars Hub, 2024)
Research Aims: This study explores the factors affecting the resistance to use metaverse shopping platforms in Sarawak, Malaysia. It focuses on four main barriers: psychological (experience and image), usage (complexity), value (economic), and risk (privacy and security). The purpose is to understand how these barriers influence users' unwillingness to adopt these platforms. Design/Methodology/Approach: The study used a quantitative approach and analysed 205 datasets from Sarawak, Malaysia, obtained from questionnaires. Preliminary analysis was done with SPSS, followed by a detailed analysis using PLS-SEM with WarpPLS 8. Research Findings: The study found that complexity, privacy and security, experience, and image barriers positively and significantly impact the resistance to use metaverse shopping platforms. However, the economic barrier was found otherwise. Theoretical Contribution/Originality: This study explores the factors influencing consumers' resistance to use metaverse shopping platforms grounded on Innovation Resistance Theory (IRT), addressing the gaps by identifying adoption barriers. This study aims to provide insights and inform strategies to overcome these barriers and increase adoption rates. Managerial Implication in the South East Asian Context: The study aims to provide insights for industry players and policymakers in Southeast Asia, especially in Malaysia. Business owners can refer to this study when considering metaverse involvement. Research Limitation & Implications: This study, which was only conducted in Sarawak, could be expanded to other Southeast Asian regions. It provides empirical evidence to the IRT, benefiting business owners and policymakers in strategy development, innovation, and decision-making for adopting the metaverse into businesses.